2020
DOI: 10.1002/ejhf.1783
|View full text |Cite
|
Sign up to set email alerts
|

The impact of palliative care on clinical and patient‐centred outcomes in patients with advanced heart failure: a systematic review of randomized controlled trials

Abstract: Aims To examine the impact of palliative care on acute care hospitalizations, survival, symptoms, and quality of life (QOL) in patients with advanced heart failure. Methods and results We conducted a systematic search of publications through CENTRAL, CINAHL, EMBASE, and MEDLINE originally up to July 2017, and then updated to June 2019. The study was registered (PROSPERO ID: CRD42017069685) prior to its initiation. Randomized controlled trials (RCTs) were included that tested an interdisciplinary palliative car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 29 publications
2
46
0
6
Order By: Relevance
“…Several recently published meta-analyses and systematic reviews point to the significant role of palliative care interventions on enhancing quality of life and reducing symptoms burden and health care cost and utilization. [161][162][163][164][165][166][167] A systematic search of 124 randomized controlled trials shows that palliative care improves outcome of many end-of-life conditions including cancer, chronic heart failure, chronic obstructive pulmonary disease, and dementia. These systematic reviews point to the effectiveness of communication and psychosocial support.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recently published meta-analyses and systematic reviews point to the significant role of palliative care interventions on enhancing quality of life and reducing symptoms burden and health care cost and utilization. [161][162][163][164][165][166][167] A systematic search of 124 randomized controlled trials shows that palliative care improves outcome of many end-of-life conditions including cancer, chronic heart failure, chronic obstructive pulmonary disease, and dementia. These systematic reviews point to the effectiveness of communication and psychosocial support.…”
Section: Methodsmentioning
confidence: 99%
“…162 Moreover, reviews of current literature show that inpatient palliative care consultations have the potential to improve patient quality of life and encourage transitions to the community, thereby relieving overburdened acute care facilities. 165 Two other recent systematic reviews of palliative care for advanced heart failure patients reveal that palliative interventions substantially reduce hospitalizations, 163 improve patientcentered outcomes, documentation of preferences, and health care utilization. 164 Along the same line, another systematic review revealed that receiving palliative care was associated with lower emergency department attendance in the last year of life for older adults.…”
Section: Methodsmentioning
confidence: 99%
“…The expected outcomes of the Nostalgic Remembering Intervention include those reflecting physiological and psychological self-regulation, as well as improved patient-centered heart failure and dyadic metrics. 68 Autonomic function is evaluated as HRV, a primary outcome in intervention research exploring the efficacy of approaches promoting feeling safe and socially connected. 69 HPA axis and immune response associated with HRV are evaluated as cortisol, C-reactive protein, and proinflammatory cytokines.…”
Section: Elements Of Nostalgic Remembering Intervention Developmentmentioning
confidence: 99%
“…151 Providing palliative care substantially reduces hospitalizations, with no clear adverse effect on survival. 152…”
Section: Self-care and Palliative Carementioning
confidence: 99%